Guided Autotransplantation of Impacted Canines Using a CAD/CAM Surgical Template - Soyoung Park; Haena Lee; Eungyung Lee; Taesung Jeong; Hyeonjong Lee; Jonghyun Shin (MDPI AG, 2023)
Autotransplantation is a potential treatment alternative when orthodontic traction of an impacted tooth is difficult. In this article, we describe two cases of guided autotransplantation of an impacted canine using a computer-aided designed and manufactured surgical template. The impacted canine was segmented on preoperative cone-beam computed tomography images to ensure a sufficient periodontal ligament space and placement of the donor tooth with the least pressure on it. The canine was virtually transposed using a simulation program considering the adjacent teeth. The surgical template, which was connected to the occlusal stop on adjacent teeth, was designed and 3D-printed with polymer resin. The recipient site was prepared using the surgical template, followed by immediate transplantation of the surgically extracted canine into the socket. The transplanted donor tooth was positioned in planned infra-occlusion to prevent occlusal interference. It was then splinted with the adjacent teeth for initial stabilization. During follow-up, one transplanted tooth showed pulp canal obliteration and the other had suspected pulp necrosis; endodontic treatment was performed. One year after the procedure, the periradicular condition of both teeth was favorable.